Correlation between CYP2C9 gene polymorphism and warfarin dose in Chinese Han population with coronary heart disease - Zuo, Qiyu; Li, Li; Zhong, Mingjing; Chen, Gengbiao; Xio, Junhui (Cellular and Molecular Biology, 2021)
This study aimed to explore the correlation between CYP2C9 gene polymorphism and warfarin dose in Chinese Han patients with coronary heart disease. The selection was made to the analysis of blood coagulation test of Chinese Han ethnic group, 200 cases of coronary heart disease patients as target group, the patients were satisfied taking warfarin INR target (in the range of 2.0 3.0), the other to select 200 cases proved by physical examination health as health group. The warfarin dose and the clinical laboratory INR after warfarin administration were taken, and the DNA of the patients was extracted and tested. The CYP2C9 genotype and allele frequency of patients in the standard group were observed, and the basic information and gene test results of the healthy group and the standard group were compared. Patients in the standard group were grouped according to the CYP2C9 and VKORC1 genotype, and the warfarin dosage was compared respectively. The number of cases of anticoagulant overdose in patients with different genotypes in the target group at the initial stage of warfarin treatment was compared. Results showed that CYP2C9*1/*2, *2/*2, *2/*3, *3/*3 genotypes were not found by detecting CYP2C9 genotype and allele frequency in the standard group. There were no significant differences in genotype and allele frequency between the standard group and the healthy group (P BBB 0 0.05). The mean daily dose of the CYP2C9*1/*3 genotype was lower than the mean daily dose of warfarin required by the CYP2C9*1/*1 genotype, and the difference was statistically significant (P < 0.05). There were significant differences in the incidence of anticoagulation overdose at the initial stage of treatment among different CYP2C9 genotypes (P < 0.05), and the incidence of an anticoagulation overdose in group *1/*3 was significantly higher than that in group *1/*1. In general, There was a correlation between CYP2C9 gene polymorphism and warfarin dose in Chinese Han population with coronary heart disease. Compared with the wilD-type (*1/*1) enzyme, the metabolic ability of warfarin in mutant CYP2C9 enzyme (mainly *1/*3 in Chinese population) decreases, and the patients were sensitive to warfarin treatment, and the dose required decreases.